PERBEDAAN CORAK PEMAHAMAN AGAMA ANTARA FUNDAMENTALISME DAN LIBERALISME SERTA DAMPAKNYA BAGI TIMBULNYA KONFLIK KEAGAMAAN - Badarus Syamsi (IAIN Ponorogo, 2014)
Abstract: Religion shapes its followers’ mind and attitudes. Belief in truth of religion often stimulates religious followers to defend such a truth claim and advocate it beyond their religious fellows. This attitude yields personalization and standardization of religious truth to justify others. This article examines fundamental different ways in understanding religion and the impacts of this to religious conflict and the rise of religious fundamentalism and liberalism. Religious values, missions and the idea of salvation often contradict with local-cultural norms and stir up interreligious horizontal conflicts. This is because followers of religion hold a strict view that only their religion is valid while others are wrong. As a result, conflict occurs inevitably. The conflict ranges from ideologies, ideas to physical violence. It should be noted that all religious schools and thoughts, be they fundamentalism or liberalism, express only a small part and relative truth of religion. Therefore, they should co-operate one another to seek the ultimate truth. Without liberalism, fundamentalism cannot find the truth and without fundamentalism, liberalism may not be unable to find the ultimate truth, God.